1988
DOI: 10.1007/bf00436251
|View full text |Cite
|
Sign up to set email alerts
|

Corn as a source of mycotoxins in Indonesian poultry feeds and the effectiveness of visual examination methods for detecting contamination

Abstract: Every truck load of corn (n = 52) entering and every batch of poultry feed (n = 290) leaving a Bogor feedmill over one year was analysed for aflatoxins, zearalenone, ochratoxin A and sterigmatocystin. Fifty loads of corn and 274 of the batches of chicken feed contained aflatoxins. Zearalenone was detected in 11 corn samples but was not found in the formulated feed. Ochratoxin A was detected in one corn sample, but not in feed. Corn can account for all of the aflatoxin in the feed since levels were always lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
2
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 12 publications
0
1
2
1
Order By: Relevance
“…It was found that 18 of 21 samples were contaminated in the range from 6.3 to 125 lg/kg. The result is in contrast to those reported by Widiastuti et al (1988a) who did not find a contamination incidence of ZON in 290 poultry feed samples. Although the high contamination of ZON is noted in poultry feed samples, poultry does not seem to be sensitive and affected by Fusarium mycotoxins including ZON (Razzazi-Fazeli, B€ ohm, Adler, & Zentek, 2003).…”
Section: Analyses With Elisa Methods and Occurrence Of Zon In Samplescontrasting
confidence: 86%
See 1 more Smart Citation
“…It was found that 18 of 21 samples were contaminated in the range from 6.3 to 125 lg/kg. The result is in contrast to those reported by Widiastuti et al (1988a) who did not find a contamination incidence of ZON in 290 poultry feed samples. Although the high contamination of ZON is noted in poultry feed samples, poultry does not seem to be sensitive and affected by Fusarium mycotoxins including ZON (Razzazi-Fazeli, B€ ohm, Adler, & Zentek, 2003).…”
Section: Analyses With Elisa Methods and Occurrence Of Zon In Samplescontrasting
confidence: 86%
“…Of 17 samples, three (17.6%) were contaminated in the range from 6.6 to 61.9 lg/kg. The result is lower than reported by Widiastuti, Maryam, Blaney, Stoltz, and Stoltz (1988a) who detected 11 (21%) of 52 samples of maize for feed from Bogor (western Java, Indonesia) to be contaminated in a large range from 1 to 13,500 g/kg, and by Widiastuti et al (1988b) who detected seven of 16 samples from the same region in a range from 1 to 14 lg/kg. Salay and Mercadante (2002) reviewed contamination of mycotoxins in maize from several regions in Brazil and noted that more than 2000 samples in six regions, ranging from 0% to 52.3% of samples, were contaminated by ZON with the maximum level ranging from 3 to 4987 lg/kg.…”
Section: Analyses With Elisa Methods and Occurrence Of Zon In Samplescontrasting
confidence: 84%
“…In Indonesia, a study conducted during 1985-1986 found approximately 96% of 52 corn samples and 95% of 290 poultry feed samples from feed mills contained aflatoxins. Moreover, ZEN and OTA were also found in 22% and 2% of the corn samples, respectively [81]. A subsequent study by the same author on the same corn samples found cyclopiazonic acid (CPA) in 81% (n = 21/26) of the samples [82].…”
Section: Mycotoxigenic Potential Of Mycotoxigenic Isolates From Two Pmentioning
confidence: 87%
“…Ainda no mesmo experimento, foi observada uma forte correlação entre a freqüência e nível de aflatoxinas com o tempo de permanência da ração nos aviários, sendo ressaltado que a concentração de aflatoxinas tende a aumentar ao longo da cadeia de produção e comercialização das rações. Widiastuti et al (1988) também analisaram amostras de milho e ração de frangos, provenientes da Indonésia, e observaram que 96% das amostras de milho e 95% das amostras de ração estavam contaminadas com aflatoxinas. Destas, AFB 1 foi a forma mais predominante, acompanhada por baixos níveis de AFB 2 , enquanto que AFG 1 e AFG 2 foram encontradas em apenas 33 e 14% de amostras de milho e 7 e 2% em amostras de ração, respectivamente.…”
Section: Ocorrência Em Milho E Raçãounclassified